Handbook on ageing with disability - Putnam, Michelle; Bigby, Christine (New York, NY : Routledge, 2021)
"Mainstream gerontological scholarship has taken little heed of people aging with disability, and they have also been largely overlooked by both disability and aging policies and service systems. The Handbook on Aging with Disability is the first to pull together knowledge about the experience of aging with disability. It provides a broad look at scholarship in this developing field and across different groups of people with disability in order to form a better understanding of commonalities across groups and identify unique facets of aging within specific groups. Drawing from academic, personal, and clinical perspectives, the chapters address topics stemming from how the aging with disability experience is framed, the heterogeneity of the population aging with disability and the disability experience, issues of social exclusion, health and wellness, frailty, later life, and policy contexts for aging with disability in various countries. Responding to the need to increase access to knowledge in this field, the Handbook provides guideposts for researchers, practitioners, and policy makers about what matters in providing services, developing programs, and implementing policies that support persons aging with long-term disabilities and their families"--
OCLC-licensed vendor bibliographic record.
Keywords: Older people -- Services for; Older people -- Care; People with disabilities -- Services for; People with disabilities -- Care; Quality of life; SOCIAL SCIENCE / Sociology / General; SOCIAL SCIENCE / Handicapped